Clinical Features, Imaging Characteristics, and Long‐term Outcome of Dogs with Cranial Meningocele or Meningoencephalocele. (28th February 2017) - Lazzerini, K.; Gutierrez‐Quintana, R.; José‐López, R.; McConnell, F.; Gonçalves, R.; McMurrough, J.; De Decker, S.; Muir, C.; Priestnall, S.L.; Mari, L.; Stabile, F.; De Risio, L.; et al.
Abstract : Background: The term meningoencephalocele (MEC) describes a herniation of cerebral tissue and meninges through a defect in the cranium, whereas a meningocele (MC) is a herniation of the meninges alone. Hypothesis/Objectives: To describe the clinical features, magnetic resonance imaging (MRI) characteristics, and outcomes of dogs with cranial MC and MEC. Animals: Twenty‐two client‐owned dogs diagnosed with cranial MC or MEC. Methods: Multicentric retrospective descriptive study. Clinical records of 13 institutions were reviewed. Signalment, clinical history, neurologic findings and MRI characteristics as well as treatment and outcome were recorded and evaluated. Results: Most affected dogs were presented at a young age (median, 6.5 months; range, 1 month – 8 years). The most common presenting complaints were seizures and behavioral abnormalities. Intranasal MEC was more common than parietal MC. Magnetic resonance imaging identified meningeal enhancement of the protruded tissue in 77% of the cases. Porencephaly was seen in all cases with parietal MC. Cerebrospinal fluid (CSF) analysis identified mild abnormalities in 4 of 11 cases. Surgery was not performed in any affected dog. Seventeen patients were treated medically, and seizures were adequately controlled with anti‐epileptic drugs in 10 dogs. Dogs with intranasal MEC and mild neurologic signs had a fair prognosis with medical treatment. Conclusion and clinical importance: Although uncommon, MC and MEC should be considered as a differential diagnosis in young dogs presenting with seizures or alterations in behavior. Medical treatment is a valid option with a fair prognosis when the neurologic signs are mild.